Neural Circuitry Underlying the Intrusion of Task-irrelevant Threat into Working Memory in Anxiety - (:unkn) unknown (My University, 2016)
Dispositional anxiety is an important risk factor for the development of anxiety and other psychological disorders. Symptoms commonly expressed by highly anxious individuals include intrusive memories, uncertainty, and worry — all occurring in the absence of immediate threat. This raises the possibility that anxious individuals have difficulty governing threat’s access to working memory, the mental workspace where goal-related information is actively retained for guiding on-going behavior. Using functional magnetic resonance imaging (fMRI) while 81 subjects completed a well-validated working memory task, I show that threat-related and neutral distracters unnecessarily gain access to working memory, as evidenced by increased neural activity in the fusiform face area and the posterior parietal cortex. Critically, this pattern was exaggerated in individuals with high levels of self-reported dispositional anxiety. Moreover, an amygdala-based circuit mediated this anxiety-related unnecessary storage. These results provide evidence for a novel neural circuit that subserves impaired working memory filtering of threat-related distracters, and sets the stage for understanding the maladaptive cognitive profile characteristic of extreme anxiety.
Keywords: Affective Neuroscience; Anxiety; Attention; FFA; Threat; Working Memory